2020
DOI: 10.1037/spq0000341
|View full text |Cite
|
Sign up to set email alerts
|

Understanding families who choose to homeschool: Agency in context.

Abstract: Many families elect to educate their children at home rather than enroll them in school. Whereas each family maintains its own reasons for deciding to homeschool, a factor for some families, including families of color, may be found in their response to institutions and systems that have historical roots in inequality, that have intentionally or unintentionally perpetuated inequitable outcomes for their children. This article considers the decision to homeschool in the context of families' efforts to regain ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Research focusing on homeschooling of children identified as gifted is sparse (see Dennison et al, 2020; Jolly et al, 2013; Jolly & Matthews, 2017, 2018, 2020a, 2020b; Logan, 2018; Winstanley, 2009). Families of gifted children have indicated that their decision to homeschool came after multiple unsatisfactory experiences with traditional schools (Jolly et al, 2013).…”
Section: Homeschooling Gifted Childrenmentioning
confidence: 99%
“…Research focusing on homeschooling of children identified as gifted is sparse (see Dennison et al, 2020; Jolly et al, 2013; Jolly & Matthews, 2017, 2018, 2020a, 2020b; Logan, 2018; Winstanley, 2009). Families of gifted children have indicated that their decision to homeschool came after multiple unsatisfactory experiences with traditional schools (Jolly et al, 2013).…”
Section: Homeschooling Gifted Childrenmentioning
confidence: 99%
“…Tilhou (2020) notes that many families value "strong family bonds, teaching faith, closely guided social interaction, and responsive pedagogy" but doubt that public education can achieve these goals (p. 75). Another reason that motivates some families is the fact that homeschooling can empower parents to ensure that their children receive the education they deserve while mitigating inequitable outcomes they might otherwise encounter (Dennison, Lasser, Awtry Madres, & Lerma, 2020). In a study of 100 homeschooling families, Baidi (2019) found that homeschooling can enable parents to best meet the needs of their children and inspire children to learn in both academic and practical contexts.…”
Section: Values Of Homeschoolingmentioning
confidence: 99%
“…(p. 34) Hirsh (2019) summarizes, "Homeschool families are hyper-autonomous units with tremendous freedom to create curriculum, redesign typical learning pathways, and build innovative partnerships" (p. 1). For example, some minority households have chosen to homeschool their children in order to circumvent the institutions that have at times perpetuated inequalities (Dennison et al, 2020). Mazama and Lundy (2013) found that many "African American homeschoolers believe a Eurocentric curriculum is bound to gravely interfere with their children's self-esteem and sense of purpose" (p. 123).…”
Section: Values Of Homeschoolingmentioning
confidence: 99%
“…Special education in both private and public school systems provides the necessary accommodations for students, but the impacts on job satisfaction and role strain raise questions about possible alternatives like homeschooling when parents express concerns about institutionalized discrimination (Contos & Tadros, 2022;Dennison et al, 2020;Gann & Carpenter, 2018;Kunzman & Gaither, 2020). Research also determined that special education teachers teaching in public schools confront discriminatory issues and have significantly different responsibilities than their private school counterparts (Gao et al, 2020;Kang et al, 2019;Olson et al, 2019;Puzio & Valshtein, 2022;Topchyan & Woehler, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Private schools also tend to have administrators offering more support for enhancing professional development outcomes among special education teachers offering accommodations in the least restrictive environments. While both educational sectors provide accommodations, their impacts continue to raise serious questions about job satisfaction and role strain when homeschooling was a working alternative (Contos & Tadros, 2022;Dennison et al, 2020;Gann & Carpenter, 2018;Kunzman & Gaither, 2020). Similarly, the extant research findings established that special education teachers confront discriminatory issues when their professional duties must practically align with traditional expectations (Gao et al, 2020;Kang et al, 2019;Olson et al, 2019;Puzio & Valshtein, 2022;Topchyan & Woehler, 2020).…”
Section: Responsibilities In Private Schoolsmentioning
confidence: 99%